Surveillance arterioveNous fistulAs using ultRasound (SONAR) trial in haemodialysis patients: a study protocol for a multicentre observational study - Samantha Hyndman; Helena Edlin; Emma Laing; Edward CF Wilson; Subash Somalanka; James Hunter; James Richards; Mohammed Hossain; Dominic Summers; Matthew Slater; Matthew Bartlett; Vasilis Kosmoliaptsis; et al. (BMJ Open)
Introduction Arteriovenous fistulas (AVFs) are considered the best and safest modality for providing haemodialysis in patients with end-stage renal disease. Only 20% of UK centres achieve the recommended 80% target for achieving dialysis of the prevalent dialysis population via permanent access (as opposed to a central venous catheter). This is partly due to the relatively poor maturation rate of newly created fistulas, with as many as 50% of fistulas failing to mature.The Surveillance Of arterioveNous fistulAe using ultRasound study will examine whether a protocolised programme of Doppler ultrasound (US) surveillance can identify, early after creation, potentially correctable problems in those AVFs that subsequently fail to mature.Methods and analysis This is a multicentre observational study that will assess newly created AVFs by Doppler US performed at 2, 4, 6 and 10 weeks after creation. The primary outcome measure will be primary fistula patency at week 10. Secondary outcome measures include: successful use of the fistula; clinical suitability for dialysis; creation of new fistula or radiological salvage; fistula thrombosis; secondary fistula patency rate and patient acceptability.Ethics and dissemination The study has been approved by the Cambridgeshire and Hertfordshire Research Ethics Committee and by the Health Research Authority (REC 18/EE/0234). The results generated from this work will be published as open access, within 3 years of trial commencement. We will also present our findings at key national/international renal meetings, as well as support volunteers at renal patient groups to disseminate the trial outcome.Trial registration number ISRCTN36033877